KADAR HAEMOGLOBIN DAN LINGKAR LENGAN ATAS PADA IBU HAMIL MELALUI PEMBERIAN BISKUIT DAUN KELOR DIWILAYAH KERJA PKM SINORANG KABUPATEN BANGGAI PROVINSI SULAWESI TENGAH - Nursidah Nur; Jamaludin Sakung; Bima (State Islamic University of Sunan Ampel, 2022)
Consuming moringa biscuits is one of the alternatives to overcome malnutrition in Indonesia. The results of modern scientific research show that moringa leaves can be a source of nutrition for all age groups.. This study aims to find out the difference in haemoglobin levels and mid-upper arm circumference in pregnant women by giving moringa leaf biscuits. This type of study is an analytic study with RCT design The study population of 70 pregnant women was divided into two groups of 35 respondents in a control group of 35 respondents in the intervention group. Sampling techniques use proportions of sampling. The Independent variables are the moringa biscuit giving, dependent variables haemoglobin levels and the size of mid-upper arm circumfrence (MUAC). Study results found an average increase in hb levels of the treatment group by 0.74 gr% with a p-value<0.05. The average increase in the MUAC size of the treatment group is 2.25 cm with a p-value of less than α = 0.05. The highest average increase in energy intake was found in the intervention group with an average increase of 174.51 kcal. Nutritional status in pregnant women such as anemia is relatively common during pregnancy because pregnant women experience hemodelusi (dilution) with a 30% to 40% increase in volume which peaks at 32 to 34 weeks of pregnancy. The provision of snacks in the form of moringa biscuits becomes an alternative to overcome nutritional problems in pregnant women is highly recommended